(untitled) (Journal of Pharmaceutical Negative Results, 2022)
All patients with the same TNM stage are treated according to the current algorithms for the clinical treatment of patients with head and neck squamous cell carcinoma (HNSCC). Patient outcomes can be considerably improved by choosing a therapy based on a patient's unique distinctions in the genetic and biological properties of the tumour. Rapid technology advancements that enable thorough molecular characterisation of malignancies quickly and affordably have improved our understanding of the molecular pathways involved in tumour transformation and HNSCC disease development. Mining genetic data to enhance tumour staging, prognosis, and personalised therapy choices for HNSCC patients has not yet become standard practice despite noteworthy accomplishments in other tumour forms. We analyse and summarise both old and new data on predictive biomarkers for HNSCC in this review, intending to potentially enhance clinical patient care shortly.